Pengaruh Kompensasi Terhadap Kepuasan Kerja Karyawan Pada PT. Dharma Guna Wibawa Di Tapung Kabupaten Kampar - Herispon, Herispon; Firdaus, Nindi Safitri (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
Abstract, This study aims to see the effect of compensation on employee job satisfaction in a company. The research method used is descriptive quantitative method, using a sample of the entire number of employees in the company as many as 35 people, and the analysis technique used is linear regression. It was found that the compensation variable prevailing in the company had a positive and significant effect on employee job satisfaction. While the magnitude of the effect given by compensation on job satisfaction is 33.7 percent, which is at the level of moderate influence. In conclusion, more attention is needed by the company on employee job satisfaction in order to increase employee satisfaction which will ultimately lead to the achievement of results or company performance.